Hub and Spoke vs. Multiple Ports of Call - World Bank (Washington, DC, 2012)
In a hub and spoke system of containerized seaborne trade, cargo to a region is delivered first to a primary hub port and then transported to its final destination, whether by sea, rail, road or inland waterways. Similarly, exports from the region are collected in the primary hub, and then transported to final destination. While these primary ports are often equipped to allow for a quick turnaround time of vessels, there are usually two primary characteristics that set them apart from other ports: the primary hubs: (a) tend to be geographically central to the region (sometimes with a substantial hinterland - that is, it attracts a considerable amount of cargo that would in any case flow through that port); and (b) can accommodate larger vessels than other ports in the region. The West and Central African coast from Mauritania to Angola is one of the few regions of the world without a dominant hub distribution port. Since the evolution of the hub and spoke concept has been driven by competitive forces to lower container unit costs, the natural question to ask is: what features in the containerized traffic between the region and Europe, the predominating trade flow, have prevented hub development?